High serum ferritin is associated with worse outcome of patients with decompensated cirrhosis - Oikonomou, Theodora (Ann Gastroenterol, 2017)
BACKGROUND: Studies in patients with decompensated cirrhosis showed a correlation between serum ferritin levels and patients’ prognosis. Besides, red blood cell distribution width (RDW) and mean platelet volume (MPV) have been associated with the severity of hepatic function. The aim of this study was to evaluate the prognostic impact of serum ferritin and RDW/MPV in the outcome [survival, death, or liver transplantation (LT)] of patients with stable decompensated cirrhosis. METHODS: Consecutive adult patients with stable decompensated cirrhosis admitted to our department between September 2010 and February 2016 were included. Serum ferritin, RDW and MPV were recorded in every patient. They were followed up and their outcome (alive, death, or LT) was evaluated. RESULTS: 192 consecutive patients with stable decompensated cirrhosis (142 men, age 54.2±12 years); at the end of follow up [12 (range: 1-64) months] 62 patients remained alive and 130 died or underwent LT. In multivariate analysis, serum ferritin (HR 1.001, 95%CI 1.00-1.002, P=0.005) and GFR (HR 0.96, 95%CI 0.92-0.99, P=0.035) were the only independent factors significantly associated with the outcome. Ferritin had low discriminative ability (AUC: 0.61) to the outcome yielding a sensitivity and specificity of 85.3% and 44.2%, respectively, at the best cut-off point (>55 ng/mL), while patients with ferritin >55 ng/mL (n=145) had a worse outcome compared to those with ferritin ≤55 ng/mL (n=47) (log rank P=0.001). RDW and MPV were not associated with the outcome. CONCLUSION: High serum ferritin, but not RDW/MPV, is associated with worse outcome in patients with established decompensated cirrhosis. However, further studies are needed to elucidate better this issue.